Inequality of Educational Opportunities in the 20 to 29 Years Old Population of Brazil and Colombia by Ethnic-Racial Self-Assessment - Viáfara López, Carlos Augusto; Serna Alvarado, Nini Johanna (Sociedad y Economía, 2015)
This paper examines the effects of racial/ethnic status on educational achievement in Brazil and Colombia. Generalized ordered logistic model were estimated for educational achievement. The results display that for Afro-descendants in Brazil and Colombia is less likely to achieve higher educational level than non Afro-descendants, but with a stronger and more significant effect in Colombia. These results suggest the presence of a pre-market discrimination in both countries, and would support the implementation of affirmative action policies in education.